Impact of Transnational Experiences - Anahi Alviso-Marino (Arabian Humanities)
Between the late 1970s and throughout the 1980s, when Yemen was still divided into two states, many Yemenis obtained scholarships to study fine arts in the Soviet Union. Future plastic artists were working on masters and doctorates in mural painting, poster design, monumental sculpture, philosophy of art and many other disciplines. After spending many years studying in the USSR, the majority of them returned to Yemen, a new unificated State after 1990. This paper focuses on the educational and cultural experiences that took place within the context of ‘socialist’ transnational solidarity, and on the variety of influences on the development of the Yemeni plastic arts movement.